2020
DOI: 10.1155/2020/3704285
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Defensin versus Leukocyte Esterase in Periprosthetic Joint Infection: An Updated Meta-Analysis

Abstract: Periprosthetic joint infection (PJI) is a devastating complication after arthroplasty. Prompt establishment of an infection diagnosis is critical but can be very challenging at present. In order to evaluate the diagnostic accuracy of alpha-defensin or leukocyte esterase for PJI, we performed systematic research in PubMed, Embase, and Cochrane Library to retrieve relevant studies. Data extraction and quality assessment were performed by two reviewers independently. A total of thirty-one eligible studies were fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
9
0
3
Order By: Relevance
“…25 Similar to calprotectin and lactoferrin, LE activity reflects the presence of white blood cells and has been developed as a rapid, inexpensive, and widely available screening test for bacteriuria. 12,26 Furthermore, LE has potential utility for simple and rapid testing in meningitis and periprosthetic joint infections in adults and spontaneous bacterial peritonitis in adults and children, 7,9,10,[27][28][29][30][31][32][33][34][35][36] offering inexpensive testing alternatives in resourcelimited countries and preventing treatment delay. Recently, Dumoulin et al 26 described the application of LE strip testing in fecal extracts and found a reasonable correlation between FLE and FC.…”
Section: Discussionmentioning
confidence: 99%
“…25 Similar to calprotectin and lactoferrin, LE activity reflects the presence of white blood cells and has been developed as a rapid, inexpensive, and widely available screening test for bacteriuria. 12,26 Furthermore, LE has potential utility for simple and rapid testing in meningitis and periprosthetic joint infections in adults and spontaneous bacterial peritonitis in adults and children, 7,9,10,[27][28][29][30][31][32][33][34][35][36] offering inexpensive testing alternatives in resourcelimited countries and preventing treatment delay. Recently, Dumoulin et al 26 described the application of LE strip testing in fecal extracts and found a reasonable correlation between FLE and FC.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Endoprothesen ist der Test nicht zuverlässig. Eine sichere Methode zum Infektnachweis ist der Nachweis von α-Defensin im Punktat [17]. Die Gramfärbung erfasst einerseits nur grampositive Erreger und ergibt aufgrund von Verklumpungen des Farbstoffs häufig falsch-positive Ergebnisse.…”
Section: Perioperative Immunsuppressive Therapieunclassified
“…Alfa defensyna jest uwalniana przez neutrofile (PMN) w odpowiedzi na obecnosć́bakterii. Test Synovasure PJI wykazuje 97 % czułości oraz 96 % specyficzności [7,13].…”
Section: Alfa-defensynyunclassified
“…Jest to enzym produkowany w neutrofilach w obecności patogenów [13]. Przeprowadzenie tego testu jest utrudnione ze względu na konieczność nieobecności krwi w probówce, ponieważ zaburza to odczyt testu.…”
Section: Esteraza Leukocytarnaunclassified